2016 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP) 2016
DOI: 10.1109/icassp.2016.7472238
|View full text |Cite
|
Sign up to set email alerts
|

An improved DOA estimation algorithm for circular and non-circular signals with high resolution

Abstract: In this paper, an improved direction-of-arrival (DOA) estimation algorithm for circular and non-circular signals is proposed. Most stateof-the-art algorithms only deal with the DOA estimation problem for the maximal non-circularity rated and circular signals. However, common non-circularity rated signals are not taken into consideration. The proposed algorithm can estimates not only the maximal non-circularity rated and circular signals, but also the common noncircularity rated signals. Based on the property o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Te K maxima referring to source DoAs can be obtained by the two-dimensional spectral search. It is observed that although the 2D-NC-MUSIC algorithm can extend the effective array aperture and greatly improve the resolution of the DoA estimation, the expensive computation cost of twodimension spectral search limits the practical application of the 2D-NC-MUSIC algorithm in the high-real-time processing scenarios [30][31][32].…”
Section: D-nc-music Algorithmmentioning
confidence: 99%
“…Te K maxima referring to source DoAs can be obtained by the two-dimensional spectral search. It is observed that although the 2D-NC-MUSIC algorithm can extend the effective array aperture and greatly improve the resolution of the DoA estimation, the expensive computation cost of twodimension spectral search limits the practical application of the 2D-NC-MUSIC algorithm in the high-real-time processing scenarios [30][31][32].…”
Section: D-nc-music Algorithmmentioning
confidence: 99%
“…Q far-field, narrowband, uncorrelated and NC sources impinge on this array from directions . The NC sources in the paper are assumed as wide-sense quasi-stationary [ 32 , 33 ] with the NC rate as [ 13 , 34 ]. Then, the received signal can be modeled as where is the observed signal vector, represents the white circular complex Gaussian noise vector with zero mean and variance , and is the steering matrix.…”
Section: Data Modelmentioning
confidence: 99%